Pemodelan Air Tanah Di Cekungan Air Tanah Umbulan Dengan Visual MODFLOW Premium 4.3 - Segel Ginting (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2010)
Umbulan wellspring is a water primary source for Surabaya region. It’s importance for people in Surabaya, so this wellspring flowing awakes continuously every years. To see behavior to change of water table happened in Umbulan Groundwater Basin has been done by groundwater modelling with Visual MODFLOW Premium 4.3 programs. These Programs has calibrated before used to groundwater modeling. Groundwater modelling analysis has done up to 2006 year and obtained water table condition result. Based on water table result in the year 2006, so it’s done scenario by increasing pumpings number for whole location either in quantity and also in region. This Scenario resulted drowdown larger ones at scenario I up to scenario III is compared with drowdown happened at scenario IV up to scenario VI.